Marketing, Narrative and Brand Strategy in Real Time: The Case of #zarastreaming - Ramírez Barredo, Belén; Guerrero González-Valerio, Beatriz (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Live streaming commerce links digital marketing with real-time social interaction, offering a personalised and engaging shopping experience. This model has been successful in China, becoming one of the fastest-growing sales channels. The launch of #zarastreaming is Inditex's first step into the Western market. Using an exploratory research methodology, this paper analyses this event in order to evaluate its relationship with brand strategy and examine the adaptation of the format outside China. A thematic and comparative analysis model is applied to the study of branded content. The results show a high degree of similarity between the pattern used by the brand to generate content on social media and the #zarastreaming event. Among the conclusions, the importance of adapting live shopping to the characteristics of the market so that it contributes positively to the brand strategy stands out